Supplementation with Low Doses of a Cod Protein Hydrolysate on Glucose Regulation and Lipid Metabolism in Adults with Metabolic Syndrome: A Randomized, Double-Blind Study - Jensen, Caroline; Fjeldheim Dale, Hanna; Hausken, Trygve; Hatlebakk, Jan Gunnar; Brønstad, Ingeborg; Lied, Gülen Arslan; Hoff, Dag Arne Lihaug (Nutrients, 2020)
The risk of cardiovascular diseases and type 2 diabetes mellitus are increased in subjects with metabolic syndrome (MetS), and hydrolyzed fish protein may have favorable effects on metabolic health. Here, we investigated the effect of 8 weeks supplementation with 4 g of cod protein hydrolysate (CPH) on glucose metabolism, lipid profile and body composition in individuals with MetS in a double-blind, randomized intervention study with a parallel-group design. Subjects received a daily supplement of CPH (n = 15) or placebo (n = 15). Primary outcomes were serum fasting and postprandial glucose levels. Secondary outcomes were fasting and postprandial insulin and glucagon-like peptide 1 (GLP-1), fasting lipid concentrations and body composition. No difference was observed between CPH and placebo for insulin, glucose or GLP-1 after 8 weeks intervention. Fasting triacylglycerol decreased in both the CPH group and placebo group, with no change between groups. Fasting total cholesterol and low-density lipoprotein cholesterol decreased significantly within both groups from baseline to study end, but no difference was observed between the two groups. In conclusion, supplementing with a low dose of CPH in subjects with MetS for 8 weeks had no effect on fasting or postprandial levels of insulin, glucose or GLP-1, lipid profile or body composition.